Analysis of galectin‐3 levels as a source of coronary heart disease risk during periodontitis - Isola, Gaetano; Polizzi, Alessandro; Alibrandi, Angela; Williams, Ray C.; Lo Giudice, Antonino (Journal of periodontal research, 2021)
Background and Objective Different evidence has shown that Galectins have a key role as modulators of cell surface functions and signaling in a wide range of inflammatory diseases during their preclinical stages. The aim of this study was to analyze the association and impact of periodontitis and coronary heart disease (CHD) on salivary and serum Galectin‐3 in patients with periodontitis and CHD. Materials and Methods For the present study, healthy controls (n = 38), periodontitis (n = 40), CHD (n = 39), and a combination of periodontitis +CHD (n = 38) patients were enrolled and analyzed. In each patient, demographic characteristics and a full‐mouth clinical periodontal examination were achieved. Moreover, serum and salivary samples were collected to assess Galectin‐3 and Endothelin‐1 (ET‐1) levels. The Jonckheere‐Terpstra p‐trend and Spearman's correlation tests as well as uni‐ and linear regression analyses were used to analyze the study data. Results Patients with periodontitis (serum, p = .003; saliva, p < .001) and periodontitis + CHD groups (serum p = .004; saliva, p < .001) had higher median serum and salivary concentrations of Galectin‐3 in comparison with CHD and healthy controls. Serum (p = .006) and salivary (p = .009) Galectin‐3 levels were significantly correlated with serum ET‐1. The multivariate regression analysis highlighted that periodontitis (p = .047) was the significant predictor of serum Galectin‐3 levels while ET‐1 (p = .028) was the significant predictor of salivary Galectin‐3 levels. Conclusion The results showed that patients with periodontitis and periodontitis + CHD presented significant higher serum and salivary Galectin‐3 levels in comparison with CHD patients and healthy subjects. Periodontitis and ET‐1 were the significant predictors of serum and salivary Galectin‐3 levels, respectively.